The Short‐Term Effects of C‐Peptide on the Early Diabetes‐Related Ultrastructural Changes to the Podocyte Slit Diaphragm of Glomeruli in Rats. (February 2015) - Nakamoto, Hiroshi; Nakayama, Kazuhiko; Emoto, Noriaki; Kajiya, Fumihiko
Abstract Objective This study aimed to investigate the structural changes in the slit diaphragm, caused by early diabetes, and the nephroprotective effect of C‐peptide. Methods Streptozotocin‐induced type 1 diabetic Wistar rats were divided into control, control plus C‐peptide, early diabetes, and early diabetes plus C‐peptide groups. C‐peptide was infused into rats for one day. The slit diaphragm component proteins podocin, CD2AP, and nephrin, were stained immunofluorescently and their distribution quantitatively analyzed by determining the overlapping area ratio. The interfoot process gap length was measured from electron microscopic images. Results Diabetic duration correlated best with the area ratio of podocin and CD2AP (r = 0.626), followed by other protein combinations, showing progressive change in the slit diaphragm structure. C‐peptide‐treatment did not alter area ratios. The interfoot process gap length was wider in diabetic rats (p < 0.05) and did not narrow with C‐peptide‐treatment in either control or diabetic rats (both p < 0.05). Conclusions Diabetes widened the interfoot process gap length and distorted the slit diaphragm structure progressively and heterogeneously in rats with early diabetes; this was not altered by C‐peptide‐treatment. The nephroprotective effect of C‐peptide in decreasing the glomerular filtration rate appears to be functional rather than structural.